2021
DOI: 10.1371/journal.pone.0245246
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of sickness absence and disability pension before and after colorectal cancer: A Swedish longitudinal population-based matched cohort study

Abstract: Objectives Working-aged colorectal cancer (CRC) patients have a much better survival, indicating the importance of their future work situation. We investigated trajectories of sickness absence and disability pension (SADP) days before and after CRC diagnosis, and risk factors associated with different trajectories. Methods A longitudinal, population-based matched cohort study of 4735 CRC survivors in Sweden aged 19–62 when first diagnosed with CRC in 2008–2011, and 18,230 matched references was conducted, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Hence, this group of young adult CCS may need extra support to prepare for and to stay in the labor market. An association between low education and higher risk of SADP later in life is well described in non-CCS cohorts [36][37][38]. We speculate that the underlying cause may be different among CCS.…”
Section: Plos Onementioning
confidence: 63%
“…Hence, this group of young adult CCS may need extra support to prepare for and to stay in the labor market. An association between low education and higher risk of SADP later in life is well described in non-CCS cohorts [36][37][38]. We speculate that the underlying cause may be different among CCS.…”
Section: Plos Onementioning
confidence: 63%
“…In this study, more comorbidities among TMD patients resulted in more days of SL and DP. This finding is not surprising and multiple comorbidities have been shown to affect the trajectory and need of social insurance benefits for other conditions as well [ 27 31 ]. Our results also show increased reliance on social insurance benefits even before diagnosis and inclusion in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that labor market participation is affected among cancer patients in general 34 and among CRC patients in particular. 30,33,[35][36][37][38][39] Several prognostic factors have been investigated in cohorts of CRC patients, but the vast majority of individual factors were investigated in only 1 or 2 studies. Previous studies have shown, that (Neo)adjuvant therapy, higher age, low educational level, and comorbidity impact labor market attachment negatively; whereas unemployment, extensive surgical resection, and postoperative complications increase the risk of work disability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown, that (Neo)adjuvant therapy, higher age, low educational level, and comorbidity impact labor market attachment negatively; whereas unemployment, extensive surgical resection, and postoperative complications increase the risk of work disability. 38,40 Furthermore, return to work is impaired by the presence of metastases, emotional distress, postoperative complications, part-time employment at baseline, and being employed in a large company. 33,41 Although statistically significant associations between working 2 years after surgery and a number of sociodemographic and clinical factors were found in this study, the main reasons why 1 in 3 CRC survivors had not resumed work after 2 years, can only be hypothesized.…”
Section: Discussionmentioning
confidence: 99%